The Influence of Quizizz and Google Form Applications on Students' Motivation and Cognitive Learning Outcomes on Human Respiratory System Material - Bobi Bobi; Tomi Hidayat; Jayanti Syahfitri (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of using the quizizz application and google form on student motivation, determine the effect of using the quizizz application and google form on students' cognitive learning outcomes in the subject of the human respiratory system for class VIII students of SMP Negeri 11 Kaur. This type of research is Quasi-Experimental (Pseudo-Experimental). The research design used in this study is nonequivalent control group design. The data analysis technique used to test the hypothesis in this study is the independent sample t-test. The results showed that there was a significant effect of the use of the Quizizz application and Google Form on student motivation and there was a significant effect of the use of the Quizizz application and Google Form on students' cognitive learning outcomes in the material on the respiratory system in humans compared to the control class. The motivation for using the Quizizz Application and Google Form is better than the control class. This can be seen from the average score of students' motivation using the Quizizz application 82.1, Google Form 75.24 and the control class 58.33, while judging from the cognitive learning outcomes of students using Quizizz application 81.66, Google Form 71.66 and control class 58.33. From the results of this study it can be concluded that the use of the Quizizz and Google Form applications in the experimental class is better than the control class which uses conventional media.